16th IHIW: Global distribution of extended HLA haplotypes. (9th January 2013) - Askar, M.; Daghstani, J.; Thomas, D.; Leahy, N.; Dunn, P.; Claas, F.; Doran, S.; Saji, H.; Kanangat, S.; Karoichane, M.; Tambur, A.; Monos, D.; et al.
Summary This report describes the project to identify the global distribution of extended HLA haplotypes, a component of 16th International HLA and Immunogenetics Workshop (IHIW), and summarizes the initial analyses of data collected. The project aims to investigate extended HLA haplotypes, compare their distribution among different populations, assess their frequency in hematopoietic stem cell unrelated donor registries and initiate an international family studies database and DNA repository to be made publicly available. HLA haplotypes compiled in immunogenetics laboratories during the evaluation of transplant candidates and related potential donors were analysed. Haplotypes were determined using the pedigree analysis tool publicly available from the National Marrow Donor Program (NMDP) website. Nineteen laboratories from 10 countries (11 laboratories from North America, five from Asia, two from Latin America and one from Australia) contributed data on a total of 1719 families comprised of 7474 individuals. We identified 10 393 HLA haplotypes, of which 1682 haplotypes included high‐resolution typing at HLA‐A, B, C, DRB1 and DQB1 loci. We also present haplotypes containing MICA and other HLA loci and haplotypes containing rare alleles seen in these families. The project will be extended through the 17th IHIW, and investigators interested in joining the project may communicate with the first author.